LOKALITAS ILMU TAJWID DALAM RISALAH MIFTAH AL-LISAN KARYA K.H. ABDUL DJAMIL NAWAWI - Fiqih Kurniawan (IAIN Syekh Nurjati Cirebon, 2019)
Historically, the practice of reading the Qur'an had already existed as Islam entered the archipelago. Unfortunately, the tendency of Qur’anic studies has long been dominated by the tafsir and translation of Qur’an. In the 20th century, the studies of the Qur’an came through a different tendency, namely Tajweed. This paper intends to examnine a treatise of “Miftah al-Lisan” written by K.H. Abdul Djamil Nawawi. This treatise is the science of Tajweed that departs from a social phenomenon, namely the community of Quranic tadarus. The media to deliver this treatise are local languages. The other characteristic of “Miftah al-Lisan” is that it does not only explain Tajweed, but it also contains laws, verbal solutions, and advice for students and teachers.